To Assess The Effectiveness of Student Empowerment on Healthy Lifestyle Practices Among Students at SRM College of Nursing, SRMIST, Kattankulathur, Chengalpattu DT. - K, Kanmani.; P, Kishore.; Keerthi Sweety. P, Krena; S, Kameswaran. (Journal of Neonatal Surgery, 2025)
Healthy lifestyle practices endeavor to prevent diseases and illnesses and to enhance an individual's general health. Today's health problems are primarily caused by inactivity and poor lifestyle. While it is true that living a healthy lifestyle can reduce mortality and disease rates, research on large populations of people shows that living a sedentary lifestyle raises the risk of a number of chronic illnesses. Adolescent students' physical activity and diet are assessed using the scale for healthy habits built in this context. The proactive handling of one's own health is regarded as health responsibility. Any form of motion is considered a physical activity. Objectives: To determine the level of knowledge and practice among adolescent students in the experimental and control groups with regard to student empowerment towards healthy lifestyle practices. To assess the impact of student empowerment on the experimental group of adolescent students' adoption of a healthy lifestyle. To compare the knowledge and behavior of adolescent pupils in the experimental and control groups on student empowerment on healthy lifestyle practices between pre- and post-test periods. To ascertain the relationship between post-test knowledge and practice regarding student empowerment in terms of practicing a healthy lifestyle and their chosen demographic characteristics./ Methodology: Quantitative research approach and Quasi Experimental Randomized Control Group Design was adopted to this study. A total of 100 adolescent students were selected by non-probability convenient sampling techniques. The study was conducted in SRM College of Nursing, SRMIST, Kattankulathur. Section- A consists of demographic data of the adolescent students participating in this study. It includes age, sex, religion, family income and occupation, living area, number of family members, and dietary pattern. Section-B: It consists of 15 semi structured multiple choice questions with four options each regarding the knowledge on physical activity and nutrition among adolescent students. Section-c: It consists of 15 semi structured multiple choice questions with four options each regarding the practice on physical activity and nutrition among adolescent students. Major Findings Of The Study: Compares the post-test level of knowledge score between experimental and control students, in experimental group, 12% of the students are having inadequate level of knowledge score, 8% of them having moderate level of knowledge score and 80% of them are having adequate level of knowledge score. In control group, 20% of the students are having inadequate level of knowledge score, 6% of them having moderate level of knowledge score and 74% of them are having adequate level of knowledge score. Conclusion: The findings revealed that the student empowerment on healthy lifestyle practice among adolescent students as more effective with the adequate knowledge gain score when compared to pretest level of knowledge. Enhanced knowledge and practice regarding student empowerment on healthy lifestyle practice should be used in developing highly effective educational programme in colleges’ areas